Clinical and radiographic periodontal parameters and release of collagen degradation biomarkers in naswar dippers. (20th September 2017) - Daood, U.; Abduljabbar, T.; Al‐Hamoudi, N.; Akram, Z.
Abstract : Background and Objective: The aim of the present study was to compare clinical periodontal parameters and to assess the release of C‐telopeptides pyridinoline cross‐links (ICTP) and C‐terminal crosslinked telopeptide (CTX) from gingival collagen of naswar (NW) and non‐ naswar (control) dippers. Material and Methods: Eighty‐seven individuals (42 individuals consuming NW and 45 controls) were included. Clinical (plaque index, bleeding on probing, probing depth and clinical attachment loss) and radiographic (marginal bone loss) periodontal parameters were compared among NW and control groups. Gingival specimens were taken from subjects in NW and control groups, assessed for ICTP and CTX levels (using ELISA) and analyzed using micro‐Raman spectroscopy. The significance of differences in periodontal parameters between the groups was determined using Kruskal‐Wallis and Mann‐Whitney U tests. The percent loss of dry mass over exposure time and the rate of release of ICTP and CTX from all groups were compared using the paired t ‐test to examine the effects of exposure time. Results: Clinical and radiographic periodontal parameters were significantly higher in the NW group than the control group ( P < .01). In the Raman spectrum, the strongest and sharpest band occurred at 1260 cm −1 amongst NW users. A Raman band at Amide I was observed with slight shifts in wave numbers. The rate of ICTP and CTX release was significantly higher in subjects from the NW group compared with those from the control group ( P < .05). Both factors, the type of groups and time, had a significant effect on release of ICTP and CTX ( P < .05). Conclusion: Within the limits of the present study, it may be concluded that clinical and radiographic periodontal parameters were worse among subjects in the NW group than in those of the control group. There is a higher degree of collagen breakdown in the connective tissue of subjects in the NW group as a result of naswar usage.